2020
DOI: 10.3892/or.2020.7685
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of lncRNA ANRIL inhibits the development of cisplatin resistance by upregulating miR‑98 in lung cancer cells

Abstract: Emerging evidence has demonstrated that abnormally expressed long non-coding (lnc) RNAs contribute to drug resistance in various types of malignancy. LncRNA antisense non-coding RNA in the inhibitor of cyclin-dependent kinase 4 locus (ANRIL) exerts oncogenic activity and acts as a key player in a variety of carcinomas, including non-small cell lung cancer. The present study aimed to investigate the functional roles of ANRIL in cisplatin (DDP) resistance of lung cancer and the underlying mechanism involved in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Though not statistically significant, SAOS2 ANRIL knockdown cells displayed a predicted trend of decreased proliferation rates under drug-naïve conditions. The effect of ANRIL expression on cancer cell proliferation observed in our study is consistent with previous reports documented in retinoblastoma, liver cancer, gastric cancer and lung cancer [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Additionally, a previous study by Li G. et al showed decreased cell proliferation under drug-naïve conditions and increased cisplatin sensitivity in U2OS cells after ANRIL knockdown [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Though not statistically significant, SAOS2 ANRIL knockdown cells displayed a predicted trend of decreased proliferation rates under drug-naïve conditions. The effect of ANRIL expression on cancer cell proliferation observed in our study is consistent with previous reports documented in retinoblastoma, liver cancer, gastric cancer and lung cancer [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Additionally, a previous study by Li G. et al showed decreased cell proliferation under drug-naïve conditions and increased cisplatin sensitivity in U2OS cells after ANRIL knockdown [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown that ANRIL expression is upregulated in osteosarcoma tissues by comparison to adjacent normal tissues and may play a role in the regulation of cell proliferation, growth, and metastasis of osteosarcoma and other cancer types [ 30 , 31 , 32 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. In relation to chemotherapeutic response, ANRIL has also been reported to promote cell chemoresistance, in multiple cancer types, to various therapeutic agents including cisplatin [ 33 , 34 , 35 , 36 , 37 , 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study, Let-7b expression was shown to be lower in the low-risk karyotype AML group and higher in the intermediate or high-risk karyotype AML group ( 51 ). The expression of Let-7 is also related to the drug resistance of leukemia; for example, miR-98 belongs to the Let-7 family, and the overexpression of miR-98 in drug-resistant cells significantly reversed drug resistance ( 52 ). It is speculated that miR-98 may be a potential approach to overcome the drug resistance of leukemia cells.…”
Section: Expression and Roles Of Let-7 In Amlmentioning
confidence: 99%